The Use of Dust Suppression on Unpaved Roads at the Mining Allotment of the Kuzbass Mine - Cherkasova Tatyana; Cherkasova Elizaveta; Tihomirova Anastasia; Andryushkov Alexey; Dormeshkin Oleg (E3S Web of Conferences, 2019)
Marker substances for the coal mining industry were identified as an information and technical reference book to the best available technologies for coal mining and processing. Inorganic dust when emitted into the atmosphere is defined as a marker substance for the coal industry. Inorganic dust emissions belong to the group of fugitive emissions which are carried out from large areas. For the solving of the mentioned problem on the territory of Mine no.12 in Kiselevsk city, it was proposed to use the Anti-dust and the Bischofit products.